Spectrometric method for determination of inorganic contaminants (arsenic, cadmium, lead and mercury) in Smooth weakfish fish. (March 2017) - Silva, T.S.; Conte, C.; Santos, J.O.; Simas, E.S.; Freitas, S.C.; Raices, R.L.S.; Quitério, S.L.
Abstract: This study aimed to investigate methodologies to quantify the elements arsenic, cadmium, lead and mercury in fish and verify the occurrence of these metals in Smooth weakfish ( Cynoscion leiarchus ), often consumed in Rio de Janeiro. Samples were freeze-dried and arsenic, cadmium and lead were quantified by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The methods were validated according to the validation procedures of the Brazilian National Institute of Metrology, Quality and Technology (Inmetro) and the European Community. The results met the acceptance criteria for validation, and the methods were suitable for detecting the elements in the following ranges: As and Hg: 1000 ng g −1, Pb: 300 ng g −1, and Cd:100 ng g −1 . The limits of detections found for As, Cd, Pb and Hg were 2.02 ng g −1, 0, 11 ng g −1 and 1, 9 ng g −1, 0, 03 ng g −1 respectively. Then samples of smooth weakfish fish was evaluated and the fish species presented levels ranging from 5.17 ng g −1 to 14.05 ng g −1 ; 119.23 ng g −1 to 272.74 ng g −1, and 6.95 ng g −1 to 10.83 ng g −1 for the elements Hg, As, and Cd, respectively. In contrast, the Pb levels were below the limits of quantification. Highlights: Implementation of ICP-OES methods of analysis for As, Cd, and Pb in fish. Implementation of method of analysis for Hg by Direct Mercury Analyzer in fish. Validate of implemented methods. Fortified Matrix was used in validation of both methods.